2019
DOI: 10.1016/j.actbio.2019.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the role of graft compliance mismatch on intimal hyperplasia using an ex vivo organ culture model

Abstract: There is a growing clinical need to address high failure rates of small diameter (< 6 mm) synthetic vascular grafts. Although there is a strong empirical correlation between low patency rates and low compliance of synthetic grafts, the mechanism by which compliance mismatch leads to intimal hyperplasia is poorly understood. To elucidate this relationship, synthetic vascular grafts were fabricated that varied compliance independent of other graft variables. A computational model was then used to estimate change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 55 publications
0
57
0
Order By: Relevance
“…Their findings suggested that the new helical graft with taper would significantly enhance helical flow, which would reduce the thrombus formation and IH. Post et al 23 focused their analysis to estimate changes in fluid flow and WSS as a function of graft compliance with the host artery and concluded that high compliance grafts displayed minimal changes in fluid flow and arterial remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings suggested that the new helical graft with taper would significantly enhance helical flow, which would reduce the thrombus formation and IH. Post et al 23 focused their analysis to estimate changes in fluid flow and WSS as a function of graft compliance with the host artery and concluded that high compliance grafts displayed minimal changes in fluid flow and arterial remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…According to several authors, graft‐vessel compliance mismatch represents a critical factor in determining the abnormal hemodynamic conditions (shear rate disturbances) leading to intimal hyperplasia. [ 30–32 ] Hence, we believe that the satisfactory patency results found in this study (i.e., 100% of subjects in the 90 days group with clinically relevant flow) might be ascribed to the similar values of radial dynamic compliance of Silkothane grafts as compared to native ovine vessels (4.8% per 100 mmHg for Silkothane grafts [ 8 ] versus 2.55–4.82% per 100 mm Hg for ovine carotid arteries [ 33,34 ] ). In contrast, ePTFE‐based grafts display lower radial compliance, ranging around 1.6% per 100 mm Hg.…”
Section: Discussionmentioning
confidence: 88%
“…Histopathology. A) H&E staining of whole sections of one representative subject for each group(30, 60, and 90 days) at the level of A1, G1, G2/G3, V2, and V3/V4, evidencing limited deposition of endoluminal matrix inside the graft; * represents a blood clot due to incorrect anti-coagulation during explant. B-D) H&E staining of significant regions of V2 in a representative subject of the 30 days group.…”
mentioning
confidence: 99%
“…Indeed, cyclic stretching induced by pulse waves at arterial pressures has been shown to play an important role in vascular cell phenotype and ECM synthesis (Lu & Kassab, ; Mao et al, ; Zhu et al, ). This dynamic stimulation is essential to improve construct development and translation to the in vivo microenvironment as it minimizes the negative effects of mechanical mismatching upon implantation (Post et al, ).…”
Section: Discussionmentioning
confidence: 99%